Compensatory and restorative mechanisms in victims in the late postblast period - S.M. Karpov; E.M. Bakhadova; A.E. Apaguni; E.N. Karpova (Неврология, нейропсихиатрия, психосоматика)
Objective: to assess restorative and compensatory mechanisms in victims of blast injury (BI) in its late period.Patients and methods. A clinical and neurophysiological examination was made in 78 blast victims, among whom there were 75 men and 3 women at the age of 30 to 48 years (mean age 37.4±3.2 years). The patients were divided into two groups: 1) 51 (65.4%) patients with BI concurrent with varying degrees of brain injury and concomitant complications; 2) 27 (34.6%) patients with BI and mainly peripheral involvement (limb amputation). Most (84%) victims were 20–40 years old. A control group consisted of 27 ageand gender-matched healthy individuals. The trend in BI sequels was traced within 3 years after injury. Cardiointervalography was employed to evaluate autonomic tone.Results. Varying degrees of adaptive processes were found in the groups under study; the neurophysiological price of traumatic impact of BI on the regulation of adaptive mechanisms in its late period was mathematically expressed. The most favorable adaptation according to autonomic support parameters and its stabilization were noted in Group 2 victims. These patients had long an autonomic imbalance with sympathetic dominance. An orthostatic test could reveal autonomic responsiveness in both groups, pointing to the breakdown of central regulatory mechanisms with emphasis to trophotropic parasympathetic dominance in the compensatory and restorative processes of autonomic support.